MOTIVASI KERJA STAF SANGGAR KEGIATAN BELAJAR (SKB) LUBUK BEGALUNG KOTA PADANG - Devista, Nova (JIV-Jurnal Ilmiah Visi, 2007)
The working motivation is a very crucial factor in accomplishing the goal of the Centre for Learning Activities program. It is influenced by various internal factors as well as external factors. This study was aimed at disclosing the working motivation of the staff at the Centre for Learning Activities in Lubuk Begalung, and finding out factors influencing the working motivation and efforts that have been practiced by the headmaster to solve various problems. A qualitative approach was utilized to answer the research problems. Data were collected by means of observation, interviews and documentation studies. The main resource person was the headmaster and expanded by a snowball technique. The data were analyzed by techniques as suggested by Miles and Huberman (1992) which consist of data reduction, presentation and drawing conclusions. Validation of data was conducted through triangulation, lengthening the observation and discussion with colleagues. The findings of this study are : (1) the working motivation of the staff of the Centre for Learning Activities is categorized as less satisfactory (2) the working motivation of the staff is influenced by many factors, such as unfavorable working climate, leadership style of the headmaster and uncertainty of reward system, and (3) some efforts that have been practiced by the headmaster are allowing the staff to get advanced degree, directing the staff and warning the staff with low achievement. It is strongly recommended to do more activities and programs to improve the working motivation of the staff.